The Mediation of Job Satisfaction and Organizational Commitment on Transformational Leadership and Employee Retention in Business Process Outsourcing Companies in Metro Manila: A Serial Mediation Analysis - Rodriguez, Joel Mark Pirote; Sergote, Jessie F.; Palallos, Lourdes; Garcia, Nelson R. (The South East Asian Journal of Management, 2025)
Research Aims: Few studies have taken into consideration transformational leadership's influence on employee retention via work satisfaction and organisational commitment, despite the fact that it has been demonstrated to positively affect organisationally relevant employee attitudes and performance. This paper fills this gap and looks into the serial mediation of these two variables in the relationship between transformational leadership and retention of employees in BPOs in Metro Manila. Design/Methodology/Approach: A quantitative serial-mediation design was used, with a sample of 400 purposively selected respondents having at least 6 months of tenure. The PLS-SEM method was used to estimate direct and indirect relationships. Research Findings: The results showed that transformational leadership enhances job satisfaction and organizational commitment, both of which contribute to employee retention. However, the full serial mediation pathway was not statistically supported, indicating very limited effects in series. Theoretical Contribution/Originality: The findings accentuate further how transformational leadership impacts employee attitudes, while also suggesting the necessity to look beyond for organizational-wide intervention for retention. Managerial Implication in the South East Asian Context: This study provided substantial data about transformational leadership. The study specifically pointed out that job satisfaction and organizational commitment are significant factors in retaining employees. The results give credence to the idea that organizations can reduce attrition and stabilize their workforce over a longer term if they nurture leadership styles that embrace empathy, communication, and empowerment. Research Limitation & Implications: Implications point to leadership training and improved working conditions as important strategies for ensuring that BPOs can sustain their workforce over the long term.